#TITLE_ALTERNATIVE# - RADIANTI (NIM 25597059); Pembimbing: Ir. Muhammad Tasrif, M.Eng., JAZIAR
Development theories in 1950's and 1960's assumed that developing countries were trapped by vicious cycle of poverty. Income percapita which is relative low in developing countries causes low saving and in turn will affect on small investment with the result that the possibility to increase the national income is very small. Foreign aid to developing countries was viewed as a means to escape from the cycle of poverty. Therefore many developing countries including Indonesia, tend to ask for loan from foreign countries to cover their deficit budget and presume, it is a shortcut to accelerate their economic growth. In fact, after more than 30 years the foreign debt which is caused by the loan policy, become a heavy burden to government, especially because of the limitation of government capacity to pay its debt service (interest and debt repayment). The objective of the study is to investigate the structure of government external debt in its budgeting process in order to recognize factors those have an unfavorable influence on Indonesia economy, and to trace policies of external debt that is able to maintain sustainable economic growth. For that, a system dynamics model of government finance, its foreign debt and its investment is developed in the study. Policies to reduce the foreign debt are tested through some simulation experiments using the model i.e: reschedulling external debt, restructuring government enterprises, applying default on a part of its foreign debt and implementing mix policy to maximize internal sources (tax and oil revenue). Essentially, these four scenarios were directed to select an alternative policy which can reduce the long run external debt burden. All policies are examined in two conditions: if the international debt sources always available for Indonesia and if the external sources are limited. Simulation results show that if foreign sources are unlimited, then government will always be able to achieve its growth target; however a gap become wider between available money and desired expenditure. Consequently, the economic growth is really leaned on external debt. Applying default is not a best choice despite it is able to reduce government debt burden. While reschedulling only shifts the current debt burden into the future and doesn't solve the overall debt problem without improving the economic performance. Policy to optimize domestic resources (oil and tax revenue, government enterprises) will provide a better impact on reducing government debt, repayment burden and be able to maintain sustainable economic growth.